Review Article on Role of Bhanga (Cannabis) in Pain Management. - Kaushik, Heena; Tomar, Brijender Singh; Chawla, Satbir Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Bhanga (Cannabis) has been an integral part of the Indian system of medicine and Indian culture from centuries. During Holi (the festival of colors) there is an increased availability and consumption of Bhanga and in Maha-Shivratri Bhanga is consumed because of its deliriant effect. However, since the consumption of Bhanga majorly falls under the category of recreational marijuana use, its exceptional medicinal values are not explored in-depth. However, during the last decade, interest in cannabis in medicinal use has been increasing. In many countries like the USA, UK etc. implementing their regulations in Bhanga (cannabis) based medicines. Bhanga is extracted from the buds, leaves, and flowers of the cannabis plant. Bhanga contains cannabinoids and is helpful in treating nausea and vomiting- mainly in the patients undergoing chemotherapy. One of the most well-known medicinal uses of cannabis products is pain reduction, especially CBD (Cannabidiol), which are quite effective in treating chronic pain. Cannabinoids can help in reducing chronic pain caused due to fibromyalgia and rheumatoid arthritis. Because of this reason research is increasing to explore the role of Bhanga (cannabis) in pain management.